Redefining Masculinity: A Cultural Study of Kabita Singha’s Pourush - Bhagyadhar Mandal, (The Creative Launcher, 2018)
Kabita Singha (1931–1999) a Bangla poet, novelist and feminist thinker was born into a literary family. She worked for some years as a schoolteacher before joining the West Bengal government as an editor. In 1965 she joined AIR. In 1981, she was invited to the Iowa International Writer’s Workshop. Although Kabita Singha is primarily known for her poetry, she authored a number of important novels in Bangla. Some of her novels are Charjan Ragi Jubati (1956), Ekti Kharap Meyer Galpo (1958, Nayika Pratinayika (1960) and Pourush (1984). Kabita Singha steps out of the age old concept of masculinity and asserts that ‘pourush’ is not an attribute of a particular gender but any individual irrespective of his or her sex, religion, education and social position does have the scope of achieving and proving this quality.